level structure of forming communicative competence among specialists of EMERCOM of Russia - Subbotina, Инна Ивановна (Chrezvychaynye situatsii: obrazovanie i nauka, 2007)
Main stages in mastering foreign speech skills of professional-oriented communicative-sufficient level on speech activity aspects on the example of graduates of higher educational establishments of EMERCOM of Russia were considered.